A Memetic Cellular Genetic Algorithm for Cancer Data Microarray Feature Selection - Rojas, Matias Gabriel (2020)
Gene selection aims at identifying a -small- subset of informative genes from the initial data to obtain high predictive accuracy for classification in human cancers. Gene selection can be considered as a combinatorial search problem and thus can be conveniently handled with optimization methods. hl{This paper proposes a Memetic Cellular Genetic Algorithm (MCGA) to solve the Feature Selection problem of cancer microarray datasets.} Benchmark gene expression datasets, i.e., colon, lymphoma, and leukaemia available in the literature were used for experimentation. MCGA is compared with other well-known metaheuristic´ strategies. The results demonstrate that our proposal can provide efficient solutions to find a minimal subset of the genes.